The association between continuous polypharmacy and hospitalization, emergency department visits, and death in older adults: a nationwide large cohort study - Chae, Jungmi; Cho, Ho Jin; Yoon, Sang-Heon; Kim, Dong-Sook (Frontiers in Pharmacology, 2024)
Background: This study aimed to investigate the association between continuous polypharmacy and hospitalization, emergency department (ED) visits, and death.Methods: This retrospective study utilized 6,443,896 patients aged between 65 and 84 years of National Health Insurance claims data from 2016 to 2018. Polypharmacy and excessive polypharmacy were defined as the concurrent use of 5 or more and 10 or more medications, respectively, for durations of both 90 days or more and 180 days or more within a 1-year observation period. The primary outcome measures included all-cause hospitalization, ED visits, and mortality. Multiple logistic regression models were used adjusting for patients' general characteristics, comorbidities, and history of hospitalization or ED visits.Results: Among 2,693,897 patients aged 65-84 years who had used medicines for 180 days or more (2,955,755 patients taking medicines for 90 days or more), the adverse outcomes were as follows: 20.5% (20.3%) experienced hospitalization, 10.9% (10.8%) visited the ED, and 1% (1%) died, respectively. In patients who exhibited polypharmacy for more than 180 days, the adjusted odds ratio of adverse outcomes was 1.32 (95% confidence interval [CI], 1.31-1.33) for hospitalization, 1.32 (95% CI, 1.31-1.33) for ED visits, 1.63 (95% CI, 1.59-1.67) for death, and that in excessive polypharmacy patients for more than 180 days was 1.85 for hospitalization, 1.92 for ED visits, and 2.57 for death, compared to non-polypharmacy patients.Our results suggest that polypharmacy in older adults might lead to negative health consequences. Thus, interventions to optimize polypharmacy may need to be implemented.